A Vocabulary of the Ancient Commentators on Aristotle : Combining the Greek–English Indexes from the Eponymous Series Spanning Works from the 2nd Century CE to Late Antiquity /: Combining the Greek–English Indexes from the Eponymous Series Spanning Works from the 2nd Century CE to Late Antiquity. (2021) - McKirahan, Richard D
No abstract available